Business model innovation in electricity supply markets: The role of complex value in the United Kingdom. (May 2016) - Hall, Stephen; Roelich, Katy
Abstract: This research investigates the new opportunities that business model innovations are creating in electricity supply markets at the sub-national scale. These local supply business models can offer significant benefits to the electricity system, but also generate economic, social, and environmental values that are not well accounted for in current policy or regulation. This paper uses the UK electricity supply market to investigate new business models which rely on more complex value propositions than the incumbent utility model. Nine archetypal local supply business models are identified and their value propositions, value capture methods, and barriers to market entry are analysed. This analysis defines 'complex value' as a key concept in understanding business model innovation in the energy sector. The process of complex value identification poses a challenge to energy researchers, commercial firms and policymakers in liberalised markets; to investigate the opportunities for system efficiency and diverse outcomes that new supplier business models can offer to the electricity system. Highlights: Business models of energy supply markets shape energy transitions. The British system misses four opportunities of local electricity supply. Nine new business model archetypes of local supply are analysed. New electricity business models have complex value propositions. A process for policy response to business model innovation is presented.